Thinking Transformational System Change. Issue 3 (2nd July 2020) - Waddock, Sandra
ABSTRACT: The dire condition of planetary systems, growing inequality, and other grand challenges seem to make system transformation, either purposeful or not, inevitable. This paper argues transformation agents using approaches that involve seeing the system and its patterns, sensemaking that constructs new narratives and stories about the system built on resonant memes, and connecting across a range of boundaries are necessary for purposeful transformation towards human and planetary wellbeing. The paper further argues that it is such purposeful transformation towards global goals around wellbeing for all (including non-humans) that is needed. MAD statement The world is in significant trouble in its future capacity to support human civilization as we know it. There is growing recognition that major and purposeful systemic transformation of human systems, e.g. economic, social, and human-nature interact, is needed. Transformation change agents can purposefully work toward system transformations using approaches of seeing and making sense of the current system to figure out where leverage points for change are, creating new stories and memes that resonate broadly through sensemaking processes, and connect actors already working toward similar ends.